The Level of Analytical Thinking, Problem Solving and its Relationship to some Variables among the Students of Karbala University - Ali AL-Mousawi, Dr. Awatef Nasser (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to reveal the level of analytic thinking and problem solving and its relationship to some variables among the students of Karbala University. The research sample consisted of (400) male and female students distributed on (8) colleges for the academic year (2018 - 2019) chosen in a random and natural manner with proportional distribution. In its five fields and consisting of (22) paragraphs, the researcher developed five alternatives for the two scales, and after conducting the validity, reliability and psychometric properties of the two scales, then applying them to the research sample. The results showed that the University of Karbala students have analytical thinking at a level (average) as well as in the scale of problem solving at the same level and that the link between the level of analytical thinking and problem solving in males is stronger than the link among females either in terms of specialization there is no difference in the strength of the link between scientific and human specialization to the level of thinking Analytical and problem solving for the students of Karbala University, Based on these results, the researcher put some suggestions and recommendations.